An ultrasensitive electrochemiluminescence aptasensor for the detection of diethylstilbestrol based on the enhancing mechanism of the metal–organic framework NH2-MIL-125(Ti) in a 3, 4, 9, 10-perylenetetracarboxylic acid/K2S2O8 system. Issue 9 (20th March 2020) - Li, Jingxian; Shan, Xueling; Jiang, Ding; Chen, Zhidong
Abstract : A novel electrochemiluminescence (ECL) aptasensor based on PTCA/NH2 -MIL-125 for the determination of diethylstilbestrol. Abstract : In this work, a sensitive and selective electrochemiluminescent aptasensor was proposed based on the enhancing mechanism of the metal–organic framework NH2 -MIL-125(Ti) in a 3, 4, 9, 10-perylenetetracarboxylic acid/K2 S2 O8 system for a diethylstilbestrol assay. Herein, 3, 4, 9, 10-perylenetetracarboxylic acid was selected as the major luminophore, and the metal–organic framework NH2 -MIL-125(Ti) displayed a large specific surface area to immobilize abundant PTCA molecules to facilitate electrochemiluminescence efficiency. Besides, the metal–organic framework NH2 -MIL-125(Ti) was used as a novel catalyst in the 3, 4, 9, 10-perylenetetracarboxylic acid/K2 S2 O8 system, which could react with the co-reactant K2 S2 O8 to produce more SO4 ˙ − . In addition, we introduced the amino-aptamer of diethylstilbestrol; due to the specific binding affinity between the aptamer and diethylstilbestrol, a selective electrochemiluminescent aptasensor for diethylstilbestrol was thus developed here. Under the optimal conditions, a wide detection range from 1.0 fM to 1.0 μM with a low detection limit of 0.28 fM ( S / N = 3) was obtained. More importantly, the residual diethylstilbestrol in water was detected by the developed aptasensor; this confirmed that this method has good performance and potential applications in real samples.